Social and nutritional factors controlling the growth of honey bee (Apis mellifera) queens - Omer Kama; Hagai Yehoshua Shpigler (PLoS ONE, 2025)
The honey bee queen is essential for colony function, laying hundreds of eggs daily and determining the colony’s genetic composition. Beekeepers cultivate and trade queens to enhance colony health and productivity. Despite its significance, artificial queen rearing in foster queenless colonies has remained largely unchanged for over a century, offering limited control over the environmental conditions influencing larval development. In this study, we developed a laboratory-based method for queen bee rearing, establishing a protocol for rearing queens in cages by nurse bees in the lab under controlled environmental conditions. We first investigated the minimal number of worker bees required to rear a single queen and found that groups of 200 workers raise queens with comparable success and weight to those reared in foster colony. As a proof of concept, we examined the impact of larval age on rearing success in our new system. We found that younger larvae developed into heavier and larger queens than older larvae, as recorded in the past using the traditional rearing method. Additionally, we assessed the influence of pollen nutrition on queen-rearing success, finding that a high pollen concentration is crucial for optimal queen development. These findings and the new method provide a foundation for studying queen bee-rearing behavior and development in the lab. We expect that it will be used to uncover factors that impact this important process in honey bee biology.